Model Pelatihan Growth Mindset Untuk Meningkatkan Kegigihan (Grit) - Gina Sania Fitri; Gian Sugiana Sugara; Dewang Sulistiana; Khairul Bariyyah (Universitas Kanjuruhan Malang, 2022)
Growth-mindset interventions emphasize that intelligence can develop when students work hard on challenging assignments. There is no research that shows the results that Growth Mindset training is effective for increasing persistence, but many studies show that the higher the degree of growth mindset, the higher the persistence of students. This pilot study aims to test the effectiveness of growth mindset training to increase persistence, which focuses on students' intelligence and abilities can be changed, so that they work harder and focus on long-term learning, appreciate the effort, can overcome challenges, and are more motivated in facing challenges with conditions challenging in a group format. This intervention was explained session by session with an experimental design with a one-group pretest-posttest design. One class with a low persistence average participated in six sessions in a group format. The pretest and posttest scores of persistence were compared which consisted of persistence, persistence, and adversity. A large effect size was found for improvement and this confirms the first hypothesis that there will be an increase in the level of persistence score from before the intervention and after the intervention. This study shows that growth mindset training is an effective treatment for increasing persistence. However, the sample size was small and this was an uncontrolled study. Therefore, it is necessary to test this intervention in trials using randomized control groups with follow-up assessments.